Habit: an exploration of shopping behaviours from transactional data - Nica-Avram, Georgiana (2020)
Some people are used to change, and to them, the constancy associated with routine might appear to be in contradiction with the postmodern world. Others may find a sense of security in loyalty towards brands or behavioural habitualness. In this context, the aim of this thesis is a better understanding of what constitutes habitualness in shopping by summarising the range and variety of behaviours emerging in two retail settings, and what is driving them. Chapter 2 has indicated opportunities for understanding the transactional and social nature of habitualness by drawing on consumer research, sociology and cognitive psychology. With data-mining approaches currently under-explored in consumer research, an opportunity also arose for investigating and measuring these behaviours via novel computational approaches. Health & beauty and grocery shopping were chosen as the focuses for the research, on the basis that in these settings, customers’ patronage and product-related behaviours are long-term, periodic and multi-modal. Using a mixed-methods sequential design, the initial scoping study presented in Chapter 5 provides an exploratory, descriptive analysis of shopping behaviours and modalities in these two retail settings. It also identifies two axes along which shopping habits develop. These denote when customers visit and what product categories they buy, and informed the studies in Chapters 6 and 7.The results of the three case studies provided evidence for the existence of foot-fall and shopping mission trends, as well as individual expressions of these habits among the customers of the two retailers in focus. Moreover, the results indicated a complex dynamic between these identified habits and contextual, impulsive and reflective factors. This analysis could not categorically identify instances of retailer, brand or product-variant loyalty, as cognitive, affective or conative valences remain unexplored. In turn, the explored exemplars and clusters opened a discussion around aspects of loyalty within the confines of the two retail settings, and how they relate to broader managerial goals and conceptualisations of loyalty in general. The value of researching shopping habits, then, is two-fold. Firstly, it helps find generalisable ‘rules’, or ‘patterns’ of behaviour across contexts and populations. If we know the who, what and where of everyday shopping habits, then we can better understand the drivers of market-wide behaviours. These, in turn, can be used as a starting point to further consumer research. A series of practical implications emerged as a result of these findings, in terms of methodological innovations, as well as managing customer relationships and their well-being.